Pemberdayaan Lokal Masyarakat Kelurahan Wonolopo Kecamatan Mijen Kota Semarang Melalui Pengembangan Desa Agrowisata - Sony Junaedi; Endah Dwi Hayati; Muslimah Muslimah (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2020)
Wonolopo is a tourist village that has been designated as tourism in the city of Semarang. The combination of natural beauty, rural community life and agricultural potential, if properly managed and taken seriously, can develop a tourist attraction for the Wonolopo village. The superior potential possessed by the Wonolopo village, especially in the fields of agriculture, plantation and tourism. Although Wonolopo has the potential to become an agro-tourism village, empirical facts in the field show that agro-tourism in the Wonolopo village is still underdeveloped. The method used to overcome the problem is to carry out a strategic program approach which is carried out in several stages, namely the Preparation Stage, the Coaching and Training Stage, the Assistance Stage and the evaluation in the formation of a joint venture. Technically, the activity plans that will be proposed in this program are (1) Workshop on changing the mindset and fostering an entrepreneurial spirit, (2) Training and mentoring on MICE-based tourism and its management, (3) Guidance and training for regional and foreign languages ​​for tour guides (local tour guide), (4) Training on agricultural product processing, mentoring, and marketing, (5) Creating a website, Facebook account, Instagram account, making leafets or tour package brochures to promote the agro-tourism village program. With this service activity, it is hoped that the Wonolopo sub-district human resources can manage its natural and cultural potential, improve the quality of life by creating better conditions for economic growth, creating jobs so that the results can actually improve the welfare of the surrounding community.